2018
DOI: 10.5334/jime.470
|View full text |Cite
|
Sign up to set email alerts
|

Developing Student Support for Open and Distance Learning: The EMPOWER Project

Abstract: European universities face great challenges dealing with twenty-first century world changes. Deep transformations are required to a wide range of lifelong learning scenarios, which are replacing traditional modes of university study and giving access to students in more flexible ways. To address the transformation in learning, the European Association of Distance Teaching Universities (EADTU) launched the EMPOWER project in 2015 so that the EADTU could share expertise of distance education universities in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 4 publications
1
33
0
2
Order By: Relevance
“…Despite the transformation of ODL into a technology-based system, the principles of support services for distance learners remain the same, in which students are engaged in learning and motivated to learn independently and autonomously. Recent research highlights the importance of academic and non-academic support and the roles of technologies to enable the development of more flexible, interactive and personalized learning environments that require new ways of providing learning support for open, distance and online students (Sánchez-Elvira Paniagua and Simpson, 2018). Earlier, Tait (2003) explained that distance students need support for three reasons, namely the needs for support, the reduction of dropout and the nature of learning.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Despite the transformation of ODL into a technology-based system, the principles of support services for distance learners remain the same, in which students are engaged in learning and motivated to learn independently and autonomously. Recent research highlights the importance of academic and non-academic support and the roles of technologies to enable the development of more flexible, interactive and personalized learning environments that require new ways of providing learning support for open, distance and online students (Sánchez-Elvira Paniagua and Simpson, 2018). Earlier, Tait (2003) explained that distance students need support for three reasons, namely the needs for support, the reduction of dropout and the nature of learning.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Students learning through an online mode need adequate learning materials and continuous support to manage learning from home (Sánchez-Elvira Paniagua & Simpson, 2018). Simpson (2013), for example, reported, students who had access to digital learning materials and were learning from home shared their lessons on blogs, commented on others' posts and asked questions to authors.…”
Section: Ict Support In Learningmentioning
confidence: 99%
“…Culture is the most influential factor for individual attitudes in accepting and using various technologies [6]. Previous studies found cross-cultural broadening of models in acceptance of technology, like technology acceptance models [7]. However, the Unified Theory of Acceptance and Use of Technology (UTAUT) model is a newer instrument that desegregates reasoned action theory, motivational models, and acceptance models [8].…”
Section: Introductionmentioning
confidence: 99%